Stress distribution of complete-arch implant-supported prostheses reinforced with silica-nylon mesh - de A. Paes, Tarcisio-José [UNESP]; Tribst, João-Paulo-Mendes [UNESP]; de Oliveira Dal Piva, Amanda-Maria [UNESP]; Amaral, Marina; Alexandre-Luiz-Souto Borges, [UNESP]; de-Cássia-Papaiz Gonçalves, Fernanda (Medicina Oral, S.L., 2019)
Background: This study evaluated the presence of a silica-nylon mesh and two cantilever lengths on the biomechanical behavior of complete-arch implant-supported prostheses. Material and Methods: Twenty-four (24) complete mandibular arch implant-supported prostheses were divided into 4 groups according to the presence of reinforcing mesh (with or without) and the cantilever length (molar-15 mm or premolar-5 mm). The specimens were submitted to strain gauge analysis (30-kgf, 10 s) at different points (molar and premolar). Three-dimensional models were created based on the in vitro specimens, and the results in the bone (microstrain), prostheses (tensile stress), implants and prosthetic screws (von-Mises stress) were evaluated using the finite element method (FEM). All materials were considered homogeneous, isotropic and linear. Strain gauge data were submitted to 3-way analysis of variance and the Tukey test (α=.05). FEM results were qualitatively analyzed using colorimetric graphs. Results: The microstrain magnitude for the prostheses with reinforcement was 519.91±359 and 583.33±661 without reinforcement (p=.001). The microstrain values for loading on the molar was 867.49±784 and on the premolar was 235.75±145. FEM corroborated with the in vitro findings for the bone behavior. The load application in the premolar showed reduced stress concentration, and a significant difference was observed between the presence or absence of the reinforcement for the prostheses. Conclusions: Silica-nylon mesh reduced the peri-implant microstrain and the prosthesis stress regardless of the cantilever extension. For temporary complete-arch implant-supported prostheses, the limitation of the cantilever to the premolar region improves the biomechanical response during load application.
Keywords: Biomechanical response; Dental implants; Finite element analysis; Prosthetic dentistry